Observation of the B-c meson in the exclusive decay B-c -> J/psi pi - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (Amer Physical Soc, 2008)
A fully reconstructed B-c -> J/psi pi signal is observed with the D0 detector at the Fermilab Tevatron p (p) over bar collider using 1.3 fb(-1) of integrated luminosity. The signal consists of 54 +/- 12 candidates with a significance that exceeds 5 standard deviations, and confirms earlier observations of this decay. The measured mass of the B-c meson is 6300 +/- 14(stat)+/- 5(syst) MeV/c(2).